Variable Costs, Fixed Costs and Entry Deterrence - Chen, Xiaotang (Université d'Ottawa | University of Ottawa, 2015)
R&D is used by firms to reduce different types of costs including variable production costs and fixed production costs. An incumbent monopolist and a potential entrant can adopt R&D to reduce their costs with bidirectional technological spillovers- spillover from the incumbent to the entrant and from the entrant to the incumbent. Thereby, R&D that affects both variable production costs and fixed production costs has an impact on the profitability of entry. This paper models entry deterrence in the presence of cost reducing R&D. The paper will discuss R&D reducing variable costs and fixed costs. Then, in order to explore the decisions of entry deterrence and entry for an incumbent monopolist and a potential entrant, this paper will focus on two aspects of entry deterrence: fixed production costs as exogenous and fixed production costs as endogenous. Then the paper will focus on the fixed production costs as endogenous to build a model to analyze the strategic behavior of the incumbent.